2016
DOI: 10.1080/21505594.2016.1195528
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of pathogenic Rift Valley fever virus strain through the chimeric S-segment encoding sandfly fever phlebovirus NSs or a dominant-negative PKR

Abstract: Rift Valley fever is a mosquito-borne zoonotic disease affecting ruminants and humans. Rift Valley fever virus (RVFV: family Bunyaviridae, genus Phlebovirus) causes abortions and fetal malformations in ruminants, and hemorrhagic fever, encephalitis, or retinitis in humans. The live-attenuated MP-12 vaccine is conditionally licensed for veterinary use in the US. However, this vaccine lacks a marker for the differentiation of vaccinated from infected animals (DIVA). NSs gene is dispensable for RVFV replication, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…To examine whether NSs genes derived from other sandfly fever phlebovirus contribute to the attenuation of RVFV, Nishiyama et al 13 generated chimeric recombinant RVFV based on the pathogenic RVFV strain ZH501 (rZH501), and they evaluated attenuation by using a mouse model. Several of the chimeras, including rZH501 encoding TOSV NSs (rZH501-TOSNSs), PTA NSs (rZH501-PTANSs), PTV Balliet strain NSs (rZH501-PTBNSs), or SFSV NSs (rZH501-SFSNSs), were inoculated into mice, and the survival rate was observed.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…To examine whether NSs genes derived from other sandfly fever phlebovirus contribute to the attenuation of RVFV, Nishiyama et al 13 generated chimeric recombinant RVFV based on the pathogenic RVFV strain ZH501 (rZH501), and they evaluated attenuation by using a mouse model. Several of the chimeras, including rZH501 encoding TOSV NSs (rZH501-TOSNSs), PTA NSs (rZH501-PTANSs), PTV Balliet strain NSs (rZH501-PTBNSs), or SFSV NSs (rZH501-SFSNSs), were inoculated into mice, and the survival rate was observed.…”
mentioning
confidence: 99%
“…These results indicate that the exogenous NSs contributes to the attenuation of RVFV, and they also suggest the applicability of SFSV NSs as a DIVA marker in the next generation of MP-12 vaccine. Another important aspect of the approach used by Nishiyama et al 13 is that it demonstrated that phlebovirus NSs proteins function as virulence factors in vivo. It was shown in the same study that 95% of mice infected with rZH501 lacking a functional NSs survived.…”
mentioning
confidence: 99%
See 3 more Smart Citations